Structure of specific precision in football players aged 10-12 - Kapidzic, A.; Molnar, S.; Radoman, M.; Smajic, M.; Tomic, B. (Serbian Journal of Sports Sciences, 2010)
Precision can be defined as a mostly innate motor ability to hit the target by a guided, thrown, struck or launched object. During the match, a footballer makes different acyclic and cyclic motions (running, walking, falling down, jumping, etc.) as he has the task to hit the ball with his leg or head and hit the target, which is either the goal (an immobile target) or his team-mate, who is most often in action (a mobile target). The complexity of this task is increased by the fact that the player is limited by time, space and action against rival players. The aim of the study was to determine the structure of specific precision in football players at the age of 10 - 12. The sample of examinees consisted of 256 footballers and the battery of 24 tests was applied to assess specific precision. The structure of specific precision was determined by factor analysis. The research presented seven latent dimensions of specific precision structure based on the analysis of their structure.